Epidemiology of BCC and cSCC in the U.K. 2013‐15. (1st September 2019) - Venables, Z.C.; Nijsten, T.; Wong, K.F.; Autier, P.; Broggio, J.; Deas, A.; Harwood, C.A.; Hollestein, L.M.; Langan, S.M.; Morgan, E.; Proby, C.; Rashbass, J.; et al.
Summary: The two most common types of skin cancer (tumour) are called basal cell carcinoma (BCC) and cutaneous squamous cell carcinoma (cSCC). BCC and cSCC have previously been removed from U.K. national cancer statistics, collected by cancer registries, because it was difficult to accurately estimate tumour counts. Improvements to registry data collection of BCC and cSCC since 2013 have resulted in the largest and most complete dataset of BCC and cSCC in the world. Therefore, the aim of this study was to provide better estimates of BCC and cSCC tumour counts using registry data in the U.K. This study confirms that skin cancers are four times more common than any other cancer in the U.K. The authors were able to show that BCCs and cSCCs affected over 210, 000 people in the U.K in 2015 with BCCs affecting 3 in 1000 people and cSCCs affecting 1 in 1000 people in 2015 alone. As they most commonly affect elderly people, it is not surprising that incidence rates are increasing by around 5% per year. Although they are less dangerous than melanomas and therefore there is less public awareness of BCC and cSCC, together, they are more than ten times more common than melanomas. This study exposes the previously unreported burden of skin cancers in the U.K. and highlights the importance of skin cancer prevention through protection against excessive ultraviolet radiation through natural (sunshine) or unnatural (tanning booths) exposure.